PERANAN BANK ASING DAN CAMPURAN TERHADAP PENGEMBANGAN UMKM DI SUMATERA UTARA - Rahmad Ardoin Purba; Coki syahwier Hasibuan (Departemen Ekonomi Pembangunan USU, 2015)
The Purpose of the study is to exemine how the role of the foreign banks and the mixture towards the development of micro, small and medium enterprises in northern Sumatra. The method used is a simple regression analysis method. The method is typically used to predict the value of the dependent variable. Variables used in this research is through micro lending small and medium enterprises by foreign banks and the mixture as the role of banks and employment as the development of micro small and medium enterprises in the province North Sumatra.The results showed that the role of foreign banks and the mixture through micro lending small and medium enterprises have a positive influence on the development of micro small and medium enterprises in the North Sumatra. Through micro lending small and medium businesess conducted by foreign banks and the mixture periodically cause employment is increasing every year so that the increase in employment is growing small and medium micro enterprises in North Sumatra.Keywords : The role of foreign and mixture banks, development of micro small and medium enterprises, North Sumatra